2017
DOI: 10.1287/mnsc.2016.2526
|View full text |Cite
|
Sign up to set email alerts
|

Monopoly Pricing in the Presence of Social Learning

Abstract: A monopolist offers a product to a market of consumers with heterogeneous quality preferences. Although initially uninformed about the product quality, they learn by observing past purchase decisions and reviews of other consumers. Our goal is to analyze the social learning mechanism and its effect on the seller's pricing decision. This analysis borrows from the literature on social learning and on pricing and revenue management.Consumers follow a naive decision rule and, under some conditions, eventually lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(41 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…It can be seen that both the dealers' type and the product quality determine the final revenue of the supply chain, and each of them is proportional to the final revenue [28][29][30]. e allocation of surplus among the brand and the dealer depends on the brand's incentive mechanisms, that is, a less well-informed brand may try to provide incentives for the more informed dealer to reveal her private quality (type) with a menu of contracts.…”
Section: Modelmentioning
confidence: 99%
“…It can be seen that both the dealers' type and the product quality determine the final revenue of the supply chain, and each of them is proportional to the final revenue [28][29][30]. e allocation of surplus among the brand and the dealer depends on the brand's incentive mechanisms, that is, a less well-informed brand may try to provide incentives for the more informed dealer to reveal her private quality (type) with a menu of contracts.…”
Section: Modelmentioning
confidence: 99%
“…They also examined how the amount and duration of discounts would affect final profitability. Crapis et al (2015) investigated social learning mechanism and its respective impact on vendor pricing decisions where customers followed intuitive decision making for purchasing a product. Given the study circumstances, he showed that customers would eventually learn about the product quality and established a technique by which the learning trajectory could be estimated using the mean-field approximation method in high demand situations.…”
Section: Analytical Model Developmentmentioning
confidence: 99%
“…Our work is most closely related to the literature in social network theory that studies a firm's optimal strategy in the presence of learning or adoption externality through some forms of local interactions by consumers, including word of mouth. Typically, these articles analyze how characteristics of the social network interact with a firm's pricing (Galeotti, ; Candogan, Bimpikis, and Ozdaglar, ; Crapis et al, ), or advertising strategy (J. Campbell, ; Galeotti and Goyal, ; Bimpikis, Ozdaglar, and Yildiz, ; Chatterjee and Dutta, ), or both (A. Campbell, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chatterjee and Dutta () assume that the firm can pay individuals to engage in word of mouth. Crapis et al (), Candogan, Bimpikis, and Ozdaglar (), and A. Campbell () consider settings where consumers pass on information if they are prepared to purchase the product. This line of analysis has been successful at relating characteristics of the social environment (such as frequency of connections/interactions, distribution of friendships, and clustering of friendships between members of the population) to a firm's strategy.…”
Section: Literature Reviewmentioning
confidence: 99%